Promoting Students’ Global Perspectives Through a Gamified e-Learning Platform - Leung, Frankie Y. W.; Lau, Martin; Wan, Kelvin; Law, Lisa; Kwong, Theresa; Wong, Eva Y. W. (Frontiers in Education, 2021)
With the rapid growth of internationalization in tertiary institutions worldwide, the development of students’ global perspectives has attracted the attention of many universities. However, this development is a challenging one due to the complicated nature of global issues and their incompatibility with traditional subject-specific boundaries of classroom teaching. Through two eTournaments organized on a proprietary gamified e-learning platform named “PaGamO”, this study examined participating students’ learning experience and their change of global perspectives due to their participation in the eTournaments. Data were collected before and after the two eTournaments, and 217 survey responses were considered to be valid and were further analyzed. The findings showed that participating students achieved the satisfaction level of enjoyment (M=3.62) and their awareness of the United Nations Sustainable Development Goals (SDGs) (M=3.96) had been improved. In addition, the findings also revealed that (i) students enjoyed and perceived better understanding of the SDGs in terms of perceptual dimensions like value-oriented and partnership-oriented, rather than the global issues about substantial threats or environmental issues; (ii) the “intrapersonal affect” of students had been significantly reduced after the eTournaments; (iii) positive significant correlations were found between the level of enjoyment and frequency of question-attempt in relation to the change of cognitive knowledge and interpersonal social interaction. The findings of this study offered some possible insights of students’ gameplay experience concerning dimensions of global perspectives, and also support the findings of prior research on how gamified e-learning platforms could contribute to the development of students’ global perspectives.